The Nigeria wealth distribution and health seeking behaviour: evidence from the 2012 national HIV/AIDS and reproductive health survey (2015)
Background: Recently, Nigeria emerged as the largest economy in Africa and the 26th in the world. However, a pertinent question is how this new economic status has impacted on the wealth and health of her citizens. There is a dearth of empirical study on the wealth distribution in Nigeria which could be important in explaining the general disparities in their health seeking behavior. An adequate knowledge of Nigeria wealth distribution will no doubt inform policy makers in their decision making to improve the quality of life of Nigerians. Method: This study is a retrospective analysis of the assets of household in Nigeria collected during the 2012 National HIV/AIDS and Reproductive Health Survey (NARHS Plus 2). We used the principal component analysis methods to construct wealth quintiles across households in Nigeria. At 5% significance level, we used ANOVA to determine differences in some health outcomes across the WQs and chi-square test to assess association between WQs and some reproductive health seeking behaviours. Result: The wealth quintiles were found to be internally valid and coherent. However, there is a wide gap in the reproductive health seeking behavior of household members across the wealth quintiles with members of households in lower quintiles having lesser likelihood (33.0%) to receive antenatal care than among those in the highest quintiles (91.9%). While only 3% were currently using modern contraceptives in the lowest wealth quintile, it was 17.4% among the highest wealth quintile (p < 0.05). Conclusion: The wealth quintiles showed a great disparity in the standard of living of Nigerian households across geo-political zones, states and rural–urban locations which had greatly influenced household health seeking behavior.